The Effect of Tens and Mc Kenzie Exercise on Pain in Cervical Root Syndrome Patients at Grandmed Hospital Lubuk Pakam in 2025 - Simson Sinuhaji; Anuhgrah Gea (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Neck pain in Cervical Root Syndrome (CRS) is caused by compression of cervical nerve roots due to trauma (e.g., whiplash injury), chronic forward head posture, or overuse. This condition radiates pain from the neck to peripheral innervated areas. McKenzie cervical exercise (extension movement) and Transcutaneous Electrical Nerve Stimulation (TENS) are interventions with potential to reduce pain through muscle strengthening and pain modulation mechanisms. Objective: To analyze the effect of combined McKenzie exercise and TENS on pain reduction in CRS patients at RS Grandmed Lubuk Pakam in 2025. Methods: A quasi-experimental study with a one-group pretest-posttest design involving 20 CRS patients. The intervention consisted of McKenzie exercise (cervical extension movements) and TENS (frequency 80–100 Hz, sensory intensity) administered twice weekly for 4 weeks (8 sessions). Pain was measured using a 0–10 mm Visual Analog Scale (VAS). Data were analyzed using a paired sample t-test (α = 0.05). Results: The mean pre-intervention pain score was 7.23 ± 1.245 (severe pain category), while the post-intervention score was 2.92 ± 1.256 (mild pain category). Statistical analysis revealed a significant reduction in pain (t = 19.23; df = 19; p < 0.001). Conclusion: The combination of McKenzie exercise and TENS significantly reduces pain (p < 0.001) in CRS patients. This intervention is recommended as a non-invasive modality for managing cervical pain.